SEMBUNG DELAN (Sphaerantus indicus L.) TERHADAP Pseudomonas solanacearum L. PENYEBAB PENYAKIT LAYU PADA TANAMAN TOMAT - Gede Darmayasa, Ida Bagus (Bumi Lestari; Vol 6 No 1, 2012)
A research entitled “Inhibitid activity of plant fractination extract of Sembung Delan (Sphaeranthus indicus L.) to the causal agent of bacterial wilt on tomato” was carried out to find out the active fraction of plant extract that responsible for bactericidal activity againt P. solanacearum L., Results of this study showed that the crude extract of S. indicus inhibited the growth of P. solanacearum L. on PDA. It was indicated by the formation of inhibition zone around the disc loaded with plant extract at concentration of 0 ppm, 10,000 ppm, 20,000 ppm, 30,000 ppm, 40,000 ppm, and 50,000 ppm. From 17 fractions obtained from fractionation, fraction No. XV (eluted with ethyl acetate 100%) contains three compunds with Rf value: 0.03; 0.23; 0.35 and fraction No. XVI (eluted with ethyl acetate 100%) contains four compunds with Rf value: 0.03; 0.14; 0.17; 0.21, effectivity inhibited the growth of P. solanacearum L
Keywords: fractination, Sembung Delan, Pseudomonas solanacearum L